Cyber operations and useful fools: the approach of Russian hybrid intelligence. Issue 7 (10th November 2018) - Gioe, David V.
Abstract: This article argues that Russian intelligence has achieved recent success in influencing democratic elections and referenda by combining the traditional Human Intelligence (HUMINT) discipline of manipulating useful fools with cutting edge cyber tactics, including hacking, phishing, social engineering, and weaponizing purloined information. This essay further argues that this synthesis yields greater effects than the sum of its parts. Given its potency, democracies and NATO members should expect to confront this type of threat more often. The 2016 American presidential election is used as a case study to conceptualize Russian hybrid intelligence, a new term reminiscent of Soviet 'complex active measures' and updated for the twenty-first century.